Deposit Insurance : A Survey of Actual and Best Practices - Garcia, G. (IMF Working Papers; Working Paper, 1999)
The paper surveys the characteristics of explicit systems of deposit insurance in 68 countries. It compares these actual practices with a set of best practices that has been adopted by IMF staff for their advice to member countries. These best practices seek to establish a system of deposit insurance that provides incentives for all parties-whether they are directly or indirectly affected by the guarantee-to keep the financial system sound. The paper discerns some convergence toward best practices in recent years, but notes several areas where improvements in the incentive structure are still necessary.